THE UTILIZATION OF BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) LEAF AS AN ANTI‑AGING - Nazliniwaty; Suryanto; Damanik, Desy Damayanti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To formulate binahong leaf extract in the microemulsion dosage form and to evaluate the anti-aging effect on the human skin. Methods: Binahong leaf extract was prepared by maceration then formulated into microemulsion dosage form with various concentrations of 0.1%, 0.3%, and 0.5%. The microemulsion preparation was prepared by adding the oil phase to the water phasehen mixed until a clear and transparent microemulsion was formed. Characterization of the dried powder included the determination of water content, water-soluble content, ethanol-soluble content, total ash content, and unsaturated acid ash content. Evaluation of microemulsion preparation included a stability test, determination of homogeneity, density, viscosity, pH, centrifugation, microemulsion type, surface tension, particle size, irritation test, and anti-aging effect test using skin analyzer. Anti-aging parameters measured included moisture, number of spots and wrinkles number. Results: Characterization results showed the water content of 7.48%, water-soluble content of 19.2%, ethanol soluble content of 9.46%, total ash content of 4.65%, and acid content of 0.58%. Microemulsion preparation of the binahong leaf extract was homogen, had low viscosity, pH 6.0–7.0, density of 1.049–1.0753 g/ml, surface tension of 35.24–38.00 dyne/cm, particle size of 364.68–632.72 nm, stable for 12 weeks storage and did not irritate the skin. The results of anti-aging effect measurements showed that the 0.5% binahong leaf extract microemulsion gave the best results. Conclusion: The dried powder of binahong leaf is qualified to be formulated. Microemulsion preparation of 0.5% binahong leaf extract showed the best anti-aging effect.